2022
DOI: 10.1002/aenm.202103332
|View full text |Cite
|
Sign up to set email alerts
|

A Valence Gradient Protective Layer for Dendrite‐Free and Highly Stable Lithium Metal Anodes

Abstract: The uncontrolled growth of Li dendrites on Li metal anodes may cause short circuit of a working cell, even electrolyte combustion and cell explosion. [4] Li dendrites may be converted to electrochemically inactive dead Li covered by SEI due to loss of electrical contact with the anode. The accumulation of dead Li may even lead to anode pulverization. [5] All these behaviors lead to a low Coulombic efficiency (CE), fast capacity fading and rapid cell failure. [6] To tackle the issues regarding Li metal anodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 74 publications
(22 reference statements)
3
26
0
Order By: Relevance
“…According to the XPS spectra, the interface layers are mainly composed of LiF, Li 2 O, LiOH, Li 2 CO 3 , Li x N, Li 2 S, Li 2 S x , and Li 2 SO x , which is supported by the results of the TOF-SIMS depth profiling (Figure S9). A peak of metallic Li appears in the Li 1s spectrum for the case of PVDF 761, but it does not exist in the case of PVDF 5130, indicating that the interface layer between the PVDF 5130-based electrolyte and a Li electrode is uniform and dense enough to fully cover the underlying metallic Li (Figure e). , This accords with the SEM results in Figure c,d. The signal of LiF in the F 1s spectrum for the case of PVDF 5130 is much stronger than that for the case of PVDF 761; therefore, more LiF, which is beneficial for the interfacial stability and battery performance, was produced due to the reaction between the PVDF 5130-based electrolyte and a Li electrode. , LiF may be originated from the dehydrofluorination of PVDF chains or the decomposition of LiFSI.…”
Section: Results and Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…According to the XPS spectra, the interface layers are mainly composed of LiF, Li 2 O, LiOH, Li 2 CO 3 , Li x N, Li 2 S, Li 2 S x , and Li 2 SO x , which is supported by the results of the TOF-SIMS depth profiling (Figure S9). A peak of metallic Li appears in the Li 1s spectrum for the case of PVDF 761, but it does not exist in the case of PVDF 5130, indicating that the interface layer between the PVDF 5130-based electrolyte and a Li electrode is uniform and dense enough to fully cover the underlying metallic Li (Figure e). , This accords with the SEM results in Figure c,d. The signal of LiF in the F 1s spectrum for the case of PVDF 5130 is much stronger than that for the case of PVDF 761; therefore, more LiF, which is beneficial for the interfacial stability and battery performance, was produced due to the reaction between the PVDF 5130-based electrolyte and a Li electrode. , LiF may be originated from the dehydrofluorination of PVDF chains or the decomposition of LiFSI.…”
Section: Results and Discussionsupporting
confidence: 85%
“…A peak of metallic Li appears in the Li 1s spectrum for the case of PVDF 761, but it does not exist in the case of PVDF 5130, indicating that the interface layer between the PVDF 5130-based electrolyte and a Li electrode is uniform and dense enough to fully cover the underlying metallic Li (Figure 3e). 34,55 This accords with the SEM results in Figure 3c,d. The signal of LiF in the F 1s spectrum for the case of PVDF 5130 is much stronger than that for the case of PVDF 761; therefore, more LiF, which is beneficial for the interfacial stability and battery performance, was produced due to the reaction between the PVDF 5130-based electrolyte and a Li electrode.…”
Section: Mechanism Analysissupporting
confidence: 91%
“…A strong peak of metallic Li at 52.4 eV appears in the Li 1s spectrum of Li/P-PE, indicating the existence of a large amount of metallic Li on the surface. 4,29 In contrast, the peak of metallic Li is much weaker in the case of Li/AP-PE, while the peak of Li + centered at 54.4 eV is much stronger, implying that the surface of the Li foil is covered with a layer of lithium compounds. 4,29 Based on the deconvolution results of the S 2p, F 1s, and N 1s spectra, it can be concluded that the interface layer for Li/AP-PE is mainly composed of Li 2 S x (161.6 and 162.6 eV), Li 2 SO 3 (169.8 eV), LiF (685.3 eV), and Li 3 N (396.9 eV).…”
Section: Resultsmentioning
confidence: 96%
“…With the increasing demand for secondary batteries with high energy and power densities, a lithium (Li) metal anode has drawn much attention during the past few decades due to its ultrahigh theoretical specic capacity. [1][2][3][4] However, owing to the high electrochemical activity of Li metal, Li metal batteries always suffer from severe anode/electrolyte corrosion and uncontrolled Li-dendrite growth, resulting in serious safety issues. If a Li metal anode is used in liquid-based batteries, the battery packs burn easily or explode violently in the case of thermal runaway.…”
Section: Introductionmentioning
confidence: 99%
“…The R ct (Fig. S26) of the Li-Ni/Li 3 N-NS@CC anode still maintains the lowest value due to the lowest Li + diffusion energy barrier of Li 3 N [ 83 ]. Exchange current density ( I 0 ) obtained from the Tafel plot can reflect charge transfer kinetics between the electrode and electrolyte components.…”
Section: Resultsmentioning
confidence: 99%